Development of Appropriate Technology for Utilizing The Effluent of Biogas Digester for Making Compost - Susi Nurweni; Aries Prasetyo; Beny Suyanto (Health Notions, 2019)
Effluent digester is potential to be composted by adding organic material (organic waste, etc.) and to accelerate maturity, inoculant effective Microorganism (EM) is required as bio decomposer in fermentation. Not only to break the chain of diseases, this organic fertilizer also economic value, sold as agricultural fertilizer.The purpose of this study is to use the effluent of biogas digester for making compost. This experimental research method using a randomized design consisting of 4 formulations each treatment replicated 3 times with 30 days maturation and the compost will be carried out physical and chemical assessment. The results showed that compost with biogas effluent material: charcoal secam: sequential organic waste with a ratio of formulas: 1 (4: 1: 1); 2 (3: 1: 1); 3 (2: 1: 1) and 4 (1: 1: 1). Physical assessment of the 4 formulas, namely temperature, pH, humidity, color, odor and texture meet the requirements of SNI 19-7030-2004. Measurement of the chemical content of formula 1 (content C: 14.36%; N: 0.98; P: 1.27; K: 1.11; C/N ratio: 14.78); 2 (content C: 17.85%; N: 2.06; P: 1.21; K: 0.88; C/N ratio: 16.91); 3 (content C: 16.14%; N: 0.84; P: 1.02; K: 1.10; C/N ratio: 14.78); 4 (content C: 16.42%; N: 0.89; P: 1.15; K: 0.88; C/N ratio: 18.52). The more use of biogas effluent produced compost with N, P, K the greater is followed by a decrease in C/N ratio and met the requirements of SNI 19-7030-2004. The results of this study can be implemented by, from and for the community, in making compost that is economically beneficial, can reduce the expenditure of chemical fertilizers. renewable energy substitutes for LPG easily and at relatively low costs. Keywords: appropriate technology; biogas digester effluent; compost